2003
DOI: 10.1053/ejvs.2002.1868
|View full text |Cite
|
Sign up to set email alerts
|

The long-term mobility and mortality of patients with peripheral arterial disease following bilateral amputation

Abstract: Amputation levels should be kept as distal as possible in the interest of mobility which is one of the primary keys to social reintegration. However reamputations to higher levels are frequent as PAD progresses. The well-known very high mortality is clearly related to generalised atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
0
28
1
1
Order By: Relevance
“…Thus, it is not surprising that the results of this study suggest even poorer functional outcomes among a largely dysvascular Veteran population than had been previously reported. Specifically, only 11 percent of Veterans in our cohort remained ambulatory after undergoing bilateral major amputations-much lower than the 38 percent rate reported by Inderbitzi et al [6]. With a similarly comorbid study population of 66 patients, Inderbitzi et al reported the mortality rate at 69 percent after 5 yr and coronary heart disease the leading cause of death [6].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Thus, it is not surprising that the results of this study suggest even poorer functional outcomes among a largely dysvascular Veteran population than had been previously reported. Specifically, only 11 percent of Veterans in our cohort remained ambulatory after undergoing bilateral major amputations-much lower than the 38 percent rate reported by Inderbitzi et al [6]. With a similarly comorbid study population of 66 patients, Inderbitzi et al reported the mortality rate at 69 percent after 5 yr and coronary heart disease the leading cause of death [6].…”
Section: Discussioncontrasting
confidence: 60%
“…The few studies published on function after bilateral major amputations have not focused on the elderly population with peripheral arterial disease (PAD) and/or diabetes typically encountered by the vascular surgeon. Nonetheless, these studies suggest that 60 percent lose ambulatory ability and 65 percent lose their ability to live independently [6][7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing age has also been associated with worse long-term outcome in previous studies [4,6,12]. These findings are unsurprising, and it is likely that longer-term outcome is related to the severity of co-existing diseases [15]. For example, Tseng et al found in a cohort of diabetic patients that continued smoking was associated with long-term mortality, but that the commonest recorded cause of death was diabetes itself [16].…”
Section: Discussionmentioning
confidence: 94%
“…[32][33][34] Responders were more likely to have an intact trial leg and, presumably therefore, to exhibit higher levels of generic but especially disease-specific HRQOL. [35][36][37][38][39][40][41] Like PREVENT III, nonresponse was associated with amputation, and this limited the information available to measure the effects of the alternative management strategies on HRQOL in this patient subgroup.…”
Section: Discussionmentioning
confidence: 99%